Strategi Index Card Match Tiga Dimensi Pada Pembelajaran IPA Kelas V SD Negeri 2 Sungai Pinang - Sinta Mariani; Aren Frima; Armi Yuneti (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to determine the science learning outcomes of fifth-grade students of SD Negeri 2 Sungai Pinang after the implementation of the index card match strategy with the help of three-dimensional significant media is complete. The research method used was quasi-experimental. The sampling technique of the population uses a saturated sampling technique. The data collection technique in this research is using a test. The steps of the analysis technique in this study are the normality test and z test with an average post-test value of 72. Based on the results of the z test value, the obtained  = 2.38 this result is compared with  = 1.64 at a significant level of 5%, namely 2.38 > 1.64, so it can be concluded that the average student learning outcomes after applying the index card match strategy assisted by three-dimensional media in science learning for class V SD Negeri 2 Sungai Pinang is significantly completed.